Racial and Educational Disparities in Dementia and Dementia-Free Life Expectancy. (25th April 2019) - Farina, Mateo P; Hayward, Mark D; Kim, Jung Ki; Crimmins, Eileen M
Abstract: Objectives: We estimate life expectancy with and without dementia for Americans 65 years and older by education and race to examine how these stratification systems combine to shape disparities in later-life cognitive health. Method: Based on the Health and Retirement Study (2000–2014), we use a multivariate, incidence-based life table approach to estimate life expectancy by cognitive health status for race–education groups. The models also simulate group differences in the prevalence of dementia implied by these rates. Results: The life table results document notable race–education differences in dementia and dementia-free life expectancy, as well as stark differences in implied dementia prevalence. At each education level, blacks can expect to live more years with dementia and they have significantly higher rates of dementia prevalence. This distribution of disparities in the older population is anchored by 2 groups—blacks without a high school diploma and whites with some college or more. Discussion: Dementia experience and dementia burden differ dramatically along race–education lines. Race and education combine to exaggerate disparities and they both have enduring effects. Future research should explicitly consider how race and education combine to influence dementia in the older American population.